Pengaruh Model PjBL Terhadap Hasil Belajar Murid pada Mata Pelajaran Akidah Akhlak di Madrasah Ibtidaiyah - Azizan, Nashran; Tanjung, Rahmadani (Darul Ilmi: Jurnal Ilmu Kependidikan dan Keislaman, 2020)
This aimed to know the influence of PjBL model toward learning results of moral lessons in knowing the prophet and apostle in IV grade of Islamic School Padangsidimpuan Angkola Julu in academic year 2019/2020 by using PjBL and Direct Instruction model. The research model used Quasi-Experimental Design with None Quivalent Control-Group Design. The used instrument is the learning result test. Data analysis used t-Test. Research result showed (1) there is the influence of PjBL model toward student's learning test on moral lesson of knowing prophet and apostle material.